Understanding Religious Moderation and Its Influence on Students' Religious Tolerance Attitudes - Ikhsan, Ilian; Afrinaldi, Afrinaldi; Hayati, Zuqriva (LP2M IAIN kUDUS, 2025)
AbstractThis study aims to analyze differences in students' understanding of religious moderation by gender and the influence of this understanding on attitudes toward religious tolerance. The study used a quantitative approach with a non-test questionnaire instrument that had been tested for validity and reliability, involving students from UIN Sjech M. Djamil Djambek Bukittinggi as respondents. The results showed differences in the level of understanding of religious moderation between male and female students, as well as a positive relationship between understanding of religious moderation and students' attitudes of religious tolerance. These findings confirm that understanding of religious moderation plays a significant role in shaping attitudes of tolerance in higher education. Scientifically, this study contributes to filling a gap in the study of religious moderation by presenting a gender perspective that has been underrepresented in previous research, and it strengthens the argument that strengthening religious moderation is a strategic factor in managing student religiosity in a multicultural society.